HEROISM OF BIELSKI BROTHERS AS JEWISH PARTISAN IN EDWARD ZWICK'S "DEFIANCE" MOVIE (2008): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - EKARIANTO, VARLIAN (2011)
The object of the study is Defiance movie by Edward Zwick. This study is aimed to show the heroism by Bielski brothers in Defiance movie by using individual psychological approach. The objective of the study is to analyze the structural elements and to analyze the movie based on the individual psychological approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the Defiance movie directed by Edward Zwick released in 2008. While the secondary data sources are other materials taken from books, journal, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound and editing are related to each other and form unity. Second, based on the individual psychological analysis, there is close relationship between the movie production and the individual factor, such as the global issues of human right and heroism. This movie also criticizes the tendency of imposing the cultural values of the dominant group over the minority.